Functional Properties and Proximate Composition of Stiff-Porridge Developed from Cooking Banana Flour - M.A., China; P.E. , Mbah; G.O, Anozie (Journal of Home Economics Research, 2024)
The study investigated the functional and proximate composition of stiff- porridge developed from cooking banana (musaacuminata). Unripe cooking banana was purchased and processed into flour. Flour samples were formulated in proportions of I00%. Functional properties of flour samples and proximate composition of the stiff-porridge products were determined. Samples were significantly different (p<0.05) from that of the 100% plantain flour. Water absorption capacity (WAC) of the samples ranged from 1.342 in sample (GCBF) per-gelatinized cooking banana flour to 3.401% in sample (GPPF). For packed bulk density, sample (RPPF) raw processed cooking banana flour had the highest value. The result followed the same pattern for swollen power. Raw processed cooking banana flour was more soluble than all other samples. Sample GPPF was highest for (LGC) least gelation capacity. Sample RPCB had higher moisture content than sample (RPPF) raw processed plantain flour, (HWBP) hot water blanched plantain flour had the highest value for ash content. There was no significant difference (P>0.05) in the fat content of all the samples. GPCB differ significantly (P<0.05) from all the samples in carbohydrate and protein content. The study showed that cooking banana can be used for such products for which plantain flour is used. The flour is desirable in terms of functional properties and proximate composition.